Feoifomicose subcutânea Subcutaneous phaeohyphomycosis - Rosane Orofino Costa (Sociedade Brasileira de Dermatologia, 2010)
São apresentadas imagens ilustrativas de um caso de feoifomicose subcutânea causada pela Exophiala jeanselmei num paciente transplantado renal. Breves comentários sobre a doença encontram-se no texto. Ressalta-se a necessidade de essa micose entrar no diagnóstico diferencial de outras dermatoses, inclusive as não infecciosas. This report shows images of a case of subcutaneous phaeohyphomycosis caused by Exophiala jeanselmei in a patient who has undergone renal transplantation. The paper comments briefly on the disease and emphasizes the need to take this mycosis into account in the differential diagnosis of other dermatoses, including non-infectious dermatoses.